2011
DOI: 10.1038/ijo.2011.237
|View full text |Cite
|
Sign up to set email alerts
|

No appetite efficacy of a commercial structured lipid emulsion in minimally processed drinks

Abstract: BACKGROUND/OBJECTIVES: Fabuless (Olibra) is a commercially structured lipid emulsion, claimed to be a food ingredient that is effective for food intake and appetite reduction. The present study assessed its efficacy in a yoghurt-based mini-drink undergoing low or minimal food manufacturing (thermal and shear) processes. SUBJECTS/METHODS: Study 1: Twenty-four healthy volunteers (16 female, 8 male; age: 18 --47 years; body mass index (BMI): 17 --28 kg m À2 ) took part in a randomised, placebo-controlled, double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Early studies conducted at the University of Ulster showed that this product decreased energy intake by an impressive 22-27% when compared to a control fat in lean, overweight and obese subjects (Burns et al 2002(Burns et al , 2001(Burns et al , 2000. These results have, unfortunately, not been replicated (Smit et al 2011;Smit et al 2012;Chan et al 2012), even by the same research group (Logan et al 2006). Smit and colleagues investigated the possible role in the processing of the emulsion, and even with minimal processing (i.e.…”
Section: Acute Intake Of Small Particle Lipids On Satietymentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies conducted at the University of Ulster showed that this product decreased energy intake by an impressive 22-27% when compared to a control fat in lean, overweight and obese subjects (Burns et al 2002(Burns et al , 2001(Burns et al , 2000. These results have, unfortunately, not been replicated (Smit et al 2011;Smit et al 2012;Chan et al 2012), even by the same research group (Logan et al 2006). Smit and colleagues investigated the possible role in the processing of the emulsion, and even with minimal processing (i.e.…”
Section: Acute Intake Of Small Particle Lipids On Satietymentioning
confidence: 99%
“…no shear and a maximum temperature of 42°C), there were effects on subjective appetite or energy intake (H. J. Smit et al 2012). This may explain why the early studies from Burns' group found positive effects, whereas later studies did not; as processing may have rendered the active ingredient in the test drinks inactive.…”
Section: Acute Intake Of Small Particle Lipids On Satietymentioning
confidence: 99%
“…Indeed, DSM (a Dutch ingredient manufacturer) has introduced an emulsionbased ingredient (Fabuless) that has been claimed to have an appetite-suppressing effect, which is reported to work by slowing down the transit time of the fat through the GIT thereby inducing the ileal brake mechanism (112). Nevertheless, other studies reported no substantial effect of this structured emulsion on food intake or appetite in human trials, which may have been due to the effects of the food matrix or processing (113,114). Clearly, further studies are needed to better understand the roles of fat droplet properties, the surrounding food matrix, and processing operations on the digestion of emulsified lipids in foods.…”
Section: Hormonal and Neurological Responsementioning
confidence: 97%
“…However, results for appetite-related measures in clinical trials with this ingredient have been highly variable (Appleton et al, 2011). However, later studiesdincluding those from the same research groupdhave been largely unable to replicate these findings in any consistent way, using a range of protocols and products, including yoghurts (Logan et al, 2006;Diepvens et al, 2007Diepvens et al, , 2008Smit et al, 2011Smit et al, , 2012Chan et al, 2012). However, later studiesdincluding those from the same research groupdhave been largely unable to replicate these findings in any consistent way, using a range of protocols and products, including yoghurts (Logan et al, 2006;Diepvens et al, 2007Diepvens et al, , 2008Smit et al, 2011Smit et al, , 2012Chan et al, 2012).…”
Section: The Challenge Of Delivering Ileal Brake Via Food Technologiesmentioning
confidence: 99%
“…Initial studies reported that yoghurts containing this ingredient reduced self-reported appetite and markedly decreased subsequent food intake (Burns et al, 2000(Burns et al, , 2001(Burns et al, , 2002. Importantly, several of the studies have suggested that any possible efficacy of the emulsion may likely be lost when it is exposed to even mild food processing conditions and formats other than yoghurt (Smit et al, , 2012Chan et al, 2012). Importantly, several of the studies have suggested that any possible efficacy of the emulsion may likely be lost when it is exposed to even mild food processing conditions and formats other than yoghurt (Smit et al, , 2012Chan et al, 2012).…”
Section: The Challenge Of Delivering Ileal Brake Via Food Technologiesmentioning
confidence: 99%